The center will hold : critical perspectives on writing center scholarship - Pemberton, Michael A.; Kinkead, Joyce A., 1954- (Utah State University Press, 2003)
In The Center Will Hold, Pemberton and Kinkead have compiled a major volume of essays on the signal issues of scholarship that have established the writing center field and that the field must successfully address in the coming decade. The new century opens with new institutional, demographic, and financial challenges, and writing centers, in order to hold and extend their contribution to research, teaching, and service, must continuously engage those challenges.